Choosing best practices for managing impacts of trawl fishing on seabed habitats and biota. Issue 2 (12th December 2019) - McConnaughey, Robert A.; Hiddink, Jan G.; Jennings, Simon; Pitcher, C. Roland; Kaiser, Michel J.; Suuronen, Petri; Sciberras, Marija; Rijnsdorp, Adriaan D.; Collie, Jeremy S.; Mazor, Tessa; Amoroso, Ricardo O; Parma, Ana M.; et al.
Abstract: Bottom trawling accounts for almost one quarter of global fish landings but may also have significant and unwanted impacts on seabed habitats and biota. Management measures and voluntary industry actions can reduce these impacts, helping to meet sustainability objectives for fisheries, conservation and environmental management. These include changes in gear design and operation of trawls, spatial controls, impact quotas and effort controls. We review nine different measures and actions and use published studies and a simple conceptual model to evaluate and compare their performance. The risks and benefits of these management measures depend on the extent to which the fishery is already achieving management objectives for target stocks and the characteristics of the management system that is already in place. We offer guidance on identifying best practices for trawl‐fisheries management and show that best practices and their likelihood of reducing trawling impacts depend on local, national and regional management objectives and priorities, societal values and resources for implementation. There is no universal best practice, and multiple management measures and industry actions are required to meet sustainability objectives and improve trade‐offs between food production and environmental protection.